Methylene Blue to Treat Protamine-induced Anaphylaxis Reactions. An Experimental Study in Pigs - Albuquerque,Agnes Afrodite S. (2016)
ABSTRACT Objective: To examine if methylene blue (MB) can counteract or prevent protamine (P) cardiovascular effects. Methods: The protocol included five heparinized pig groups: Group Sham -without any drug; Group MB - MB 3 mg/kg infusion; Group P - protamine; Group P/MB - MB after protamine; Group MB/P - MB before protamine. Nitric oxide levels were obtained by the nitric oxide/ozone chemiluminescence method, performed using the Nitric Oxide Analizer 280i (Sievers, Boulder, CO, USA). Malondialdehyde plasma levels were estimated using the thiobarbiturate technique. Results: 1) Groups Sham and MB presented unchanged parameters; 2) Group P - a) Intravenous protamine infusion caused mean arterial pressure decrease and recovery trend after 25-30 minutes, b) Cardiac output decreased and remained stable until the end of protamine injection, and c) Sustained systemic vascular resistance increased until the end of protamine injection; 3) Methylene blue infusion after protamine (Group P/MB) - a) Marked mean arterial pressure decreased after protamine, but recovery after methylene blue injection, b) Cardiac output decreased after protamine infusion, recovering after methylene blue infusion, and c) Sustained systemic vascular resistance increased after protamine infusion and methylene blue injections; 4) Methylene blue infusion before protamine (Group MB/P) - a) Mean arterial pressure decrease was less severe with rapid recovery, b) After methylene blue, there was a progressive cardiac output increase up to protamine injection, when cardiac output decreased, and c) Sustained systemic vascular resistance decreased after protamine, followed by immediate Sustained systemic vascular resistance increase; 5) Plasma nitrite/nitrate and malondialdehyde values did not differ among the experimental groups. Conclusion: Reviewing these experimental results and our clinical experience, we suggest methylene blue safely prevents and treats hemodynamic protamine complications, from the endothelium function point of view.